2021
DOI: 10.1177/10760296211048808
|View full text |Cite
|
Sign up to set email alerts
|

Significance of MPV, RDW and PDW with the Severity and Mortality of COVID-19 and Effects of Acetylsalicylic Acid Use

Abstract: We aimed to investigate association between mean platelet volume (MVP), platelet distribution width (PDW) and red cell distribution width (RDW) and mortality in patients with COVID-19 and find out in which patients the use of acetylsalicylic acid (ASA) affects the prognosis due to the effect of MPV on thromboxan A2. A total of 5142 patients were divided into those followed in the intensive care unit (ICU) and those followed in the ward. Patient medical records were examined retrospectively. ROC analysis showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
19
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 39 publications
(50 reference statements)
3
19
1
Order By: Relevance
“…However, it is suggested that platelet/large-cell-cell ratio (PLCR) (Daniels et al, 2021) is a better marker than MPV and PDW, and platelet-to-lymphocyte ratio (PLR) (Asan et al, 2021) is a better marker than platelet count. However, see counter conclusions in (Aydinyilmaz et al, 2021; Lippi et al, 2021).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, it is suggested that platelet/large-cell-cell ratio (PLCR) (Daniels et al, 2021) is a better marker than MPV and PDW, and platelet-to-lymphocyte ratio (PLR) (Asan et al, 2021) is a better marker than platelet count. However, see counter conclusions in (Aydinyilmaz et al, 2021; Lippi et al, 2021).…”
Section: Discussionmentioning
confidence: 86%
“…However, it is suggested that platelet/large-cell-cell ratio (PLCR) (Daniels et al, 2021) is a better marker than MPV and PDW, and platelet-to-lymphocyte ratio (PLR)(Asan et al, 2021) is a better marker than platelet count. However, see counter conclusions in(Aydinyilmaz et al, 2021;Lippi et al, 2021).Other factors not selected by our composite ranking in Table4include gender, monocyte, MCH/MCV (mean corpuscular hemoglobin/volumn). Male gender seems to be a risk for severity/mortality(Jin et al, 2022), though the effect size can be weak(Ortolan et al, 2020; Mukherjee and Pahan, 2021).…”
mentioning
confidence: 86%
“…However, it is suggested that platelet/large-cell-cell ratio (PLCR) ( Daniels et al, 2021) is a better marker than MPV and PDW, and platelet-to-lymphocyte ratio (PLR) ( Asan et al, 2021) is a better marker than platelet count. However, see counter conclusions in ( Aydinyilmaz et al, 2021 , Lippi et al, 2021 .…”
Section: Discussionmentioning
confidence: 87%
“…This decrease may be due to the direct effect of infection on bone marrow function and its correlated cytokines storm, which causes destruction in bone marrow progenitor cells and inhibition of platelet synthesis (26). MPV is considered an important indicator of both proinflammatory and prothrombotic conditions that is influenced by IL-1, IL-6, and other related cytokines, which regulate thrombopoiesis and cause the production of new immature platelets by the side of platelets destruction (27,28).The elucidation of risk factors leading to kidney impairment in COVID-19 infection is important for physicians to manage their patients better. Our data revealed that patients in the severe COVID-19 illness group were significantly older, had a higher BMI, and their symptoms had lasted longer than the non-severe group.…”
Section: Discussionmentioning
confidence: 99%